Pengaruh Kompensasi Finansial, Motivasi Eksternal Dan Disiplin Terhadap Kinerja Karyawan Pada CV. Alif Media Informatika - Nosi Purwanti; Suseno Hendratmoko; Endah Kurniawati (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to explain the effect of financial compensation, external motivation and discipline on employee performance at CV. Alif Media Informatics. The analysis technique uses statistical tests through validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t tests, F tests with SPSS version 16.0 tools. Sampling technique saturated sample, with the number of respondents 32 people. Based on the research results obtained by researchers from the multiple linear regression equation Y = -2.606 + 0.421X1 + 0.534X2 + 0.292X3. The results of the analysis carried out, the results of the study show that the financial compensation variable has a significant effect on employee performance, the external motivational variable has a significant effect on employee performance, the disciplinary variable has a significant effect on employee performance, and the results of financial compensation, external motivation and discipline simultaneously have a significant effect on employee performance. The results of the analysis of the value of R2 = 0.917 or 91.7%.